The book of man : readings on the path to manhood - Bennett, William J. (William John), 1943- (Nashville, Tenn. : Thomas Nelson, 2011)
This book explores the life of men in various contexts: work, play, prayer, war, home, and friendship. Using essays and stories, myths and history, to bring life to the subject, Bennett defines what a man should be, how he should live, and to what he should aspire.
Let's bring back heroes -- Man in war -- Man at work -- Man in play, sports, and leisure -- Man in the polis -- Man with woman and children -- Man in prayer and reflection --
Includes bibliographical references and index.
Keywords: Men -- Conduct of life; Character -- Case studies